Crop Yields in European Agroforestry Systems: A Meta-Analysis - Ivezić, Vladimir; Yu, Yang; Werf, Wopke van der (Frontiers in Sustainable Food Systems, 2021)
Agroforestry is the practice of integrating woody vegetation with crops and/or livestock production in order to strengthen ecological services on farmland and achieve a more multi-functional agricultural system. Crop yields determine economic outcomes when trees are young, but information on yields is scattered in the literature and a quantitative overview of crop yields in European agroforestry systems is lacking. We therefore synthesized published information on crop yields in European agroforestry systems, using meta-analysis. A systematic review of the literature was conducted, highlighting quantitative information on yields is available only for traditional Dehesa systems in Spain and Portugal and for modern alley cropping experiments, mostly in northern Europe. Relative cereal crop yields in alley cropping systems (systems with tree rows with interspersed crop strips) were 96% of sole crop yield at tree planting. Crop yields in alley cropping decreased on average with 2.6% per year over the first 21 years of the tree stand, indicating increasing competitive effects of the trees with their age. On the other hand, studies in traditional Dehesa and Montado systems in Southern Europe showed no negative influence of the trees on crop production, indicating that competition between crops and trees plays a less important role in those systems than in alley cropping. Overall, the systematic review showed a need for more experimental data to further substantiate the benefits of agroforestry and elucidate optimal agroforestry practices under European conditions.